2014
DOI: 10.13183/jcrg.v3i2.78
|View full text |Cite
|
Sign up to set email alerts
|

Kappa Agreement of Emergency Department Triage Scales; A Systematic Review and Meta-Analysis

Abstract: The aim of this review was to compare the reliability of existing triage scales. The research question was that, using kappa value as reliability measure, in adult ED patients to what extent did clinicians' triage ratings agree with eachother or with a gold standard? Methods: The search was limited to studies on adult patients (≥15 years) visiting EDs for somatic reasons and to English and Persian studies that have reported kappa. Studies solely on geriatric patients, computerized triage, telephone triage, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Triage reliability studies at the time were commonly analysed with kappa (κ) statistics, un-weighted (κ) or weighted (κW), linear (LκW) or quadratic (QκW), indicating a need for consensus on the method, in order to assess and compare the reliability of the triage scales and systems (159), even if it there has been recommendations to apply both un-weighted and quadratic weighted kappa statistics to enable comparison (160). Weighted kappa statistics imply that different weights are given to the disagreements, which is why the weighted kappa statistics usually have higher agreement because disagreements are more likely to be only one level, not several levels (132).…”
Section: Study IIImentioning
confidence: 99%
See 2 more Smart Citations
“…Triage reliability studies at the time were commonly analysed with kappa (κ) statistics, un-weighted (κ) or weighted (κW), linear (LκW) or quadratic (QκW), indicating a need for consensus on the method, in order to assess and compare the reliability of the triage scales and systems (159), even if it there has been recommendations to apply both un-weighted and quadratic weighted kappa statistics to enable comparison (160). Weighted kappa statistics imply that different weights are given to the disagreements, which is why the weighted kappa statistics usually have higher agreement because disagreements are more likely to be only one level, not several levels (132).…”
Section: Study IIImentioning
confidence: 99%
“…As the focus of the comparative aim of the study and earlier studies of RETTS© have applied Fleiss kappa (κ) statistics (145,154), this was the natural choice. However, as there is no consensus on how to measure reliability, it is important to have provided a thorough description of the case mix and method (159,160). All analysis in the study was conducted with de-identified data, de-identified by the researcher.…”
Section: Study IIImentioning
confidence: 99%
See 1 more Smart Citation